2014
DOI: 10.11648/j.ajhr.s.2014020501.21
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Work Related Musculoskeletal Pain among Professional Drivers in the Service of a Tertiary Institution

Abstract: Abstract:Musculoskeletal pain (MSP) is usually work related and it is a common phenomenon among several occupations.This study aimed at determining the prevalence and pattern of work related musculoskeletal pain (WRMSP) among drivers at a Nigerian tertiary institution. An adapted Nordic musculoskeletal pain questionnaire (NMSPQ,) was distributed to all the professional drivers who were staff of Obafemi Awolowo University, Ile Ife, Osun State, Nigeria. The response rate was 90.9%. The data were analyzed using d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 19 publications
0
2
0
2
Order By: Relevance
“…5 Also, Ojo et al (2014) found similar results that 77% of the bus drivers in Nigeria reported that they had experienced WRMSDs at some time. [7][8][9][10][11][12][13][14] The higher prevalence among bus drivers in the present study suggests that they are exuberantly predisposed to WRMSDs. This can be due to number In present study, the prevalence of low back pain was highest among the bus drivers that is 30.3%, then neck pain 17.3%, knee pain 14.7%, shoulder 6.3%, ankle and feet 5.7%, upper back 4%, hip and thigh 4%, elbow 1.3% and wrist and hand 1.3%.…”
Section: Discussionmentioning
confidence: 99%
“…5 Also, Ojo et al (2014) found similar results that 77% of the bus drivers in Nigeria reported that they had experienced WRMSDs at some time. [7][8][9][10][11][12][13][14] The higher prevalence among bus drivers in the present study suggests that they are exuberantly predisposed to WRMSDs. This can be due to number In present study, the prevalence of low back pain was highest among the bus drivers that is 30.3%, then neck pain 17.3%, knee pain 14.7%, shoulder 6.3%, ankle and feet 5.7%, upper back 4%, hip and thigh 4%, elbow 1.3% and wrist and hand 1.3%.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the present study showed that back pain (21.38%) and joint pain (26.48%) in drivers and car operators had a relatively high prevalence. Based on the results of the previous studies, the prevalence of MSDs was observed among drivers between 21% and 77%, 6,31 which may have related to the fact that MSDs among drivers are exposure to whole-body vibration, long-term driving, and incorrect or poor driver’s seat 6 . Moreover, MSDs are very prevalent in farmers 3,32.…”
Section: Discussionmentioning
confidence: 98%
“…La prévalence de la lombalgie était de 68,89% dans notre étude. Contrairement aux études de Ojo et al [10], Akinpelu et al [11] au Nigéria dont les prévalences sont proches des nôtres, nos résultats sont supérieurs aux 23% rapportés par Ndiaye et al [13] dans une étude similaire au Sénégal Cette différence pourrait s’expliquer par le mode de transport. La lombalgie survient donc chez des sujets relativement jeunes et en pleine activité professionnelle, ce qui pourrait être un handicap à l’exercice de leur profession.…”
Section: Discussionunclassified
“…Les travailleurs des secteurs du bâtiment et du transport constituent les catégories professionnelles les plus exposées avec des prévalences variant entre 20,5 et 60,4% [8, 9]. En 2014 au Nigéria, une étude réalisée chez les conducteurs de véhicules de transport avait trouvé des prévalences de 50,5% dans l’Etat d’Osun et de 64,8% en 2011 à Ibadan [10, 11]. Au Bénin, le fort taux de chômage a donné naissance depuis quelques années au phénomène de taxi moto, communément appelé «Zémidjan» et leur nombre ne cesse de s’accroitre avec une forte concentration dans les milieux urbains, tels que Porto-Novo, la capitale administrative.…”
Section: Introductionunclassified